Syntaxonomical review of Cytisetea scopario-striati communities in central Spain - Gavilán, Rosario G.; Vilches de la Serna, Beatriz; Fernández-González, Federico (Lazaroa, 2011)
A syntaxonomical study was carried out using techniques of multivariate analysis on the nanophanerophytic vegetation of Genistées included in the class Cytisetea scopario-striati, in the central Iberian Peninsula. 700 relevés -both published and unpublished- have been analysed using various types of classifications and ordinations in different stages. For this vast territory a total of 15 associations have been recognised, distributed into the four alliances traditionally recognised for the area: Retamion sphaerocarpae, Genistion floridae, Genistion polygaliiphyllae and Ulici europaei-Genistion polygaliiphyllae. The concepts of subassociation and variant recently developed have been applied in the syntaxonomical nomenclature. Of these three subassociations are proposed as new.